Ricci solitons in a generalized weakly (Ricci) symmetric D-homothetically deformed Kenmotsu manifold - Adara M. Blaga; Kanak Kanti Baishya; Nihar Sarkar (Annales Universitatis Paedagogicae Cracoviensis: Studia Mathematica, 2019)
The object of the present paper is to investigate the nature of Ricci solitons on D-homothetically deformed Kenmotsu manifold with generalized weakly symmetric and generalized weakly Ricci symmetric curvature restrictions.